2014
DOI: 10.1111/cge.12497
|View full text |Cite
|
Sign up to set email alerts
|

BRCA1 and BRCA2 mutations and the risk for colorectal cancer

Abstract: Women who carry a BRCA1 or BRCA2 mutation are at high risk of breast and ovarian cancer, and may be at moderately increased risk of other cancer types. This review examines studies to date that have evaluated the risk of BRCA1 and BRCA2 mutations for colorectal cancer. Accurate knowledge of colorectal cancer risk in BRCA1/2 carriers is important, because colonoscopy screening can prevent colorectal cancer through the removal of adenomatous polyps. Most studies that have identified an increased risk for colorec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
3
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(55 citation statements)
references
References 54 publications
(88 reference statements)
1
50
3
1
Order By: Relevance
“…Notably, these associated diseases, which are already well known, were followed by ‘colorectal cancer’, whose association with BRCA1 is not widely known (see Figure 3C). Interestingly, recent studies have reported that the risk for colorectal cancer is increased in female carriers of BRCA1 mutations (19,20), which validates the gene-to-disease association predicted by COEXPEDIA.…”
Section: Case Studiessupporting
confidence: 70%
“…Notably, these associated diseases, which are already well known, were followed by ‘colorectal cancer’, whose association with BRCA1 is not widely known (see Figure 3C). Interestingly, recent studies have reported that the risk for colorectal cancer is increased in female carriers of BRCA1 mutations (19,20), which validates the gene-to-disease association predicted by COEXPEDIA.…”
Section: Case Studiessupporting
confidence: 70%
“…Interestingly, the proband also has a germline BRCA1 mutation. Although some data has pointed toward a possible increased CRC risk in young BRCA1 carriers [9], current guidelines do not support increased CRC screening in BRCA1 carriers [10], and to our knowledge there is no known association between pathogenic BRCA1 mutations and colonic polyposis. Additionally, we are not aware of concurrent GREM1 (chromosome 15q13) and BRCA1 (chromosome 17q21) mutations, nor is there, to our knowledge, evidence that these mutations are influencing each other at the germline level or having epistatic interactions.…”
Section: Discussionmentioning
confidence: 99%
“…18Y20 It was reported that the BRCA2 polymorphism related to the risk of many cancers, including breast cancer and ovarian cancer. 20 The association between BRCA2 Arg372His polymorphism and ovarian cancer risks has been extensively studied. However, the results have been inconsistent.…”
Section: Discussionmentioning
confidence: 99%
“…18Y20 Germline mutations in BRCA1/2 are highly penetrant ovarian cancer, conferring lifetime risks of up to 40% (BRCA1) and 20% (BRCA2) for ovarian cancer. 20 In the BRCA2 gene, ARG372HIS is the only amino acid changing polymorphism with a rare allele frequency of greater than 6% and was named as rs144848. BRCA2 ARG372HIS increased the risk of breast cancer and has been reported in HH homozygotes in a large case control study.…”
mentioning
confidence: 99%